HUBUNGAN KEKUATAN OTOT LENGAN DAN BAHU TERHADAP HASIL LEMPAR CAKRAM PADA SISWA KELAS XI SMA NEGERI I KOTO KAMPAR HULU - Juita, Ardiah Juita; ', Aprinaldi; ', Ramadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The purpose of this study was to determine the relationship of the arm and shoulder muscle strength with discus throw results in class XI students of SMAN 1 Koto Kampar Hulu.This fieldwork in the background the background of a survey conducted on students of SMAN 1 Koto Kampar Hulu, it can be seen that the arm muscle strength affects the throwing distance is done by students. In addition, the strength of the shoulder also affect the discus throw distances do. he population in this study was the total number of students of class XI of SMAN 1 Koto Kampar Hulu. Samples were taken from the population because the sample is representative of the population . In this study population of 20 students, the entire population sampled to get better research results.Based on research conducted at SMAN 1 Koto Kampar Hulu gives the meaning of the power of the arm and shoulder muscles to the discus throw results provide knowledge that muscle strength has a significant influence . with less use of expanding dynamometer and discus throwing was done at 8.10 % influenced by factors force the arm and shoulder muscles and the rest influenced by other factors Keywords : Relationships, Strength, Arm and Shoulder Muscles, SMAN 1 Koto Kampar Hulu.